ANALISIS PENGENDALIAN PERSEDIAAN PARFUM AMBU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY - Daffa Maulana Asviara; Abizard Haykal, Aji Dewa Abdullah, Paduloh (ADISAM PUBLISHER, 2023)
The Economic Order Quantity research method aims to be used when achieving inventory levels at minimum cost and better quality. This research method is carried out in stages, with several stages that must be carried out including the preparation part, data collection, data processing, data analysis, discussion of research, and sources of material from books and the internet. With the results obtained Raw Material Purchase Frequency F = 18. So, the frequency of purchasing raw materials is carried out 18 times in one year.